Philosophical dissertation: a didactic strategy between orality and writing (2011)
The field of the didactics of philosophy has been marked by different theoretical and practical positions. This article attempts to further the theorization on the use of philosophical dissertation as a practical strategy, reconstructing the ideas of professor Miguel Angel Gomez Mendoza. Likewise, we propose dissertation as an oral practice, based on the educational practices and argumentative field that pertain to philosophy.